"O desenvolvimento de uma Professora Estagiária em busca da sua identidade docente" - Marisa dos Santos Peneda de Sousa (2024)
The Professional Internship took place during the 2nd year of the Master's Degree in Teaching Physical Education in Basic and Secondary Education, at the Faculty of Sports of the University of Porto, in a Cooperating School. Through the practical context, accompanied and guided by the Cooperating Teacher and the Supervising Teacher, it was possible to develop new skills and learn more about the different contents of Physical Education Teaching. In the school environment I developed some functions and tasks, where reflection became my loyal friend, allowing me to respond to conflicts and problems encountered. This Internship Report aims to present and analyze my path as a Trainee Teacher, reflecting on the challenges encountered and how they were overcome. It consists of seven chapters. Starting with the introduction, where I explain the organization of the different topics and then with the "Personal Framework" and "Institutional Framework". Its structure is based on the three main areas of the Professional Internship: Organization and Management of Teaching and Learning (Area 1), Participation in School and Relationship with the Community (Area 2) and the area of Professional Development (Area 3). Area 1 covers the topics of the 10th Year curriculum, planning and teaching management. Area 2 corresponds to my participation in School Sports and in EC training and activities. Area 3 includes academic training to complement the Diploma and my Research Study entitled "Analysis of the evolution of teacher teaching effectiveness factors when teaching handball in a 10th year class". At the end of the Internship Report, I present the "Final Considerations" including a brief conclusion of the Professional Internship.